2018
DOI: 10.1016/j.bbamem.2017.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous membrane interaction of amphipathic peptide monomers, self-aggregates and cargo complexes detected by fluorescence correlation spectroscopy

Abstract: Peptides able to translocate cell membranes while carrying macromolecular cargo, as cell-penetrating peptides (CPPs), can contribute to the field of drug delivery by enabling the transport of otherwise membrane impermeable molecules. Formation of non-covalent complexes between amphipathic peptides and oligonucleotides is driven by electrostatic and hydrophobic interactions. Here we investigate and quantify the coexistence of distinct molecular species in multiple equilibria, namely peptide monomer, peptide sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Moreover, we demonstrated that the presence of TAMRA-Tat, TAMRA-Tat-NR2B9c, and TAMRA-Tat- N -dimer boosted the cell uptake of 3–5 kDa FITC-dextran. Complexation between the peptides and FITC-dextran could, in principle, facilitate cell uptake of the latter, as exploited for intracellular delivery of oligonucleotides [ 40 , 41 ]. However, TAMRA-Tat-NR2B9c and TAMRA-Tat- N -dimer did not co-localize with FITC-dextran upon cell uptake, excluding that FITC-dextran uptake occurs only when complexed with the peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we demonstrated that the presence of TAMRA-Tat, TAMRA-Tat-NR2B9c, and TAMRA-Tat- N -dimer boosted the cell uptake of 3–5 kDa FITC-dextran. Complexation between the peptides and FITC-dextran could, in principle, facilitate cell uptake of the latter, as exploited for intracellular delivery of oligonucleotides [ 40 , 41 ]. However, TAMRA-Tat-NR2B9c and TAMRA-Tat- N -dimer did not co-localize with FITC-dextran upon cell uptake, excluding that FITC-dextran uptake occurs only when complexed with the peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Among the currently researched molecules, a group of particular interest to photochemists and physicists includes particles with photophysical properties related to the phenomenon of dual fluorescence. The mechanisms responsible for the spectroscopic properties of such molecules tend to contradict certain well established theories, e.g., Kasha’s principle [ 1 , 2 , 3 ]. The phenomenon’s significance is evident particularly in the physicochemical and spectroscopic perspective, and considerable efforts are now being made to provide a consistent theoretical description of the same.…”
Section: Introductionmentioning
confidence: 99%
“…The coexistence of distinct molecular species (monomers, self-aggregates, peptide/oligonucleotide) in complexes of Fl-PF14/cyanine5-siRNA was studied by fluorescence correlation spectroscopy (FCS) and fluorescence cross-correlation spectroscopy (FCCS) in solution and at the plasma membrane of live cells. The ratio of the complex components varied with the pH, the peptide concentration and the proximity to the plasma membrane, suggesting “that the diverse cellular uptake mechanisms, often reported for amphipathic CPPs, might result from the synergistic effect of peptide monomers, self-aggregates and cargo complexes at the plasma membrane” [ 148 ].…”
Section: Mechanismsmentioning
confidence: 99%